It is currently Wed Dec 13, 2017 2:21 am


All times are UTC [ DST ]




Post new topic Reply to topic  [ 3 posts ] 
Author Message
PostPosted: Thu Jul 07, 2016 12:51 pm 

Joined: Mon Nov 09, 2015 12:29 am
Posts: 31
Show that

\(\displaystyle \int_{-\infty }^{\infty }\int_{-\infty }^{\infty }{\rm sign}(x)\,{\rm sign}(y)e^{-\frac{x^2+y^2}{2}}\sin (xy)\,dx\,dy=2\sqrt{2}\log (1+\sqrt{2})\).


Top
Offline Profile  
Reply with quote  

PostPosted: Thu Jul 07, 2016 12:52 pm 

Joined: Wed Nov 11, 2015 12:47 pm
Posts: 13
A small comment, with a very brief examination we can easily deduce that $$\int_{-\infty}^{\infty}\int_{-\infty}^{\infty}{\rm{sign}}(x)\,{\rm{sign}}(y)e^{-\frac{x^2+y^2}{2}}\sin(xy) \;dx\;dy=4\int_{0}^{\infty}\int_0^\infty e^{-\frac{x^2+y^2}{2}}\sin(xy)\;dx\;dy\,.$$


Top
Offline Profile  
Reply with quote  

PostPosted: Thu Jul 07, 2016 12:54 pm 

Joined: Wed Nov 11, 2015 12:47 pm
Posts: 13
Computation of \(\displaystyle \int_{0}^{\infty}\int_{0}^{\infty}\mathbb{e}^{-\frac{x^2+y^2}{2}}\sin(xy)\;\mathbb{d}x\;\mathbb{d}y\).

----------------------------------------------------------------------------------------------------------------

\[\begin{eqnarray*}\int_{0}^{\infty} \int_{0}^{\infty}\mathbb{e}^{-\frac{x^2+y^2}{2}}\sin(xy)\;\mathbb{d}x\;\mathbb{d}y &=& \int_{0}^{\infty}\int_{0}^{\infty}\mathbb{e}^{-\frac{x^2+y^2}{2}}\sum_{k=0}^{\infty}\frac{(-1)^{k}(x\cdot y)^{2k+1}}{(2k+1)!}\;\mathbb{d}x\;\mathbb{d}y\\ &=& \sum_{k=0}^{\infty}\frac{(-1)^{k}}{(2k+1)!}\int_{0}^{\infty}\int_{0}^{\infty}\mathbb{e}^{-\frac{x^2+y^2}{2}}\left(x\cdot y\right)^{2k+1}\;\mathbb{d}x\;\mathbb{d}y\\ &=& \sum_{k=0}^{\infty}\frac{(-1)^{k}}{(2k+1)!}\left(\int_{0}^{\infty}\mathbb{e}^{-\frac{x^2}{2}}x^{2k+1}\;\mathbb{d}x\right)\left(\int_{0}^{\infty}\mathbb{e}^{-\frac{y^2}{2}}y^{2k+1}\;\mathbb{d}y\right)\\&=&\sum_{k=0}^{\infty}\frac{(-1)^{k}}{(2k+1)!}\left(\int_{0}^{\infty}\mathbb{e}^{-\frac{x^2}{2}}x^{2k+1}\;\mathbb{d}x\right)^{2}\\&=&\sum_{k=0}^{\infty}\frac{(-1)^{k}}{(2k+1)!}\left(\int_{0}^{\infty}\frac{\mathbb{e}^{-x}\left(\sqrt{2x}\right)^{2k+1}}{\sqrt{2x}}\;\mathbb{d}x\right)^{2}\\&=&\sum_{k=0}^{\infty}\frac{(-1)^{k}}{(2k+1)!}\left(\int_{0}^{\infty}\mathbb{e}^{-x}\left(2x\right)^{k}\;\mathbb{d}x\right)^{2}\\&=& \sum_{k=0}^{\infty}\frac{(-1)^{k}}{(2k+1)!}2^{2k}\left(\int_{0}^{\infty}\mathbb{e}^{-x}x^{k}\;\mathbb{d}x\right)^{2}\\&=&\sum_{k=0}^{\infty}\frac{(-1)^{k}}{(2k+1)!}2^{2k}\Gamma(k+1)^{2}\\&=& \sum_{k=0}^{\infty}\frac{(-1)^{k}2^{2k}(k!)^2}{(2k+1)!}\\&=&\frac{\textrm{arcsinh}(1)}{\sqrt{2}} \end{eqnarray*}\]

so \(\displaystyle \int_{0}^{\infty}\int_{0}^{\infty}\textrm{sign}(x)\,\textrm{sign}(y)\mathbb{e}^{-\frac{x^2+y^2}{2}}\sin(xy)\;\mathbb{d}x\;\mathbb{d}y=4\frac{\textrm{arcsinh(1)}}{\sqrt{2}}=2\sqrt{2}\textrm{arcsinh}(1)=2\sqrt{2}\log(1+\sqrt{2})\).


Top
Offline Profile  
Reply with quote  

Display posts from previous:  Sort by  
Post new topic Reply to topic  [ 3 posts ] 

All times are UTC [ DST ]


Mathimatikoi Online

Users browsing this forum: No registered users and 1 guest


You cannot post new topics in this forum
You cannot reply to topics in this forum
You cannot edit your posts in this forum
You cannot delete your posts in this forum
You cannot post attachments in this forum

Search for:
Jump to:  
cron
Powered by phpBB® Forum Software © phpBB Group Color scheme created with Colorize It.
Theme created StylerBB.net